A EDIFICIAÇÃO DO POSTULADO GEOMORFOLÓGICO E SUA CONTRIBUIÇÃO AO PLANEJAMENTO AMBIENTAL - Lucas Prado Osco; Rodrigo Coladello Oliveira; Marcos Norberto Boin (Universidade do Oeste Paulista, 2014)
This article's main objective is to rescue the geomorphological origin of thought, in order to address works that led to the advent of the science. For that, we discuss in particular the authors responsible for contributing to consolidation of the geomorphological knowledge. The synthesis of this information, organized during the course of the text, highlight the collaboration of several works on the functional analysis of landscape elements. The adopted methodology focused on an analysis and survey of authors and bibliographical works about the geomorphological science over the past centuries. Therefore, the elements raised in the study contributed to the advent of the evaluation and diagnosis of the physical environment, necessary presupposition for measures such as environmental planning. The article focuses on that aspect, in order to relate the geomorphological study as an instrument necessary for integrated landscape analysis.